Treatment and survival of supratentorial and posterior fossa ependymomas in adults. (June 2016) - Nuño, Miriam; Yu, Jeffrey J.; Varshneya, Kunal; Alexander, Julia; Mukherjee, Debraj; Black, Keith L.; Patil, Chirag G.
Highlights: Grade II tumors occupied posterior fossa (75%) while anaplastic were mostly supratentorial (77%). More anaplastic tumors were treated with radiotherapy and chemotherapy than grade II. Radiotherapy and chemotherapy did not provide an overall survival benefit. Abstract: Ependymoma is a rare primary brain or spinal cord tumor that arises from the ependyma, a tissue of the central nervous system. This study analyzed a large cohort of adult supratentorial and posterior fossa ependymoma tumors in order to elucidate factors associated with overall survival. We utilized the USA National Cancer Database to study adult World Health Organization grade II/III supratentorial and posterior fossa ependymoma patients treated between 1998 and 2011. Overall survival was estimated by the Kaplan–Meier method and factors associated with survival were determined using a multivariate Cox proportional hazards model. Among 1318 patients, 1055 (80.0%) had grade II and 263 (20.0%) anaplastic tumors located in the posterior fossa (64.3%) and supratentorial region (35.7%). Overall average age was 44.3 years, 48.0% of patients were female, 86.5% were Caucasian, and 36.8% underwent near/gross total surgical resection. Radiotherapy was given to 662 patients (50.8%) and 75 (5.9%) received chemotherapy. Older age at diagnosis (hazard ratio [HR] 1.51, p < 0.0001), high tumor grade (HR 1.82, p = 0.005), and large tumor size (HR 1.66, p = 0.008) were associated with poor survival. Females compared to males (HR 0.67, p = 0.03) and patients with posterior fossa tumors versus supratentorial (HR 0.64, p = 0.04) had a survival advantage. Our study showed that older patients, with supratentorial tumors, and high histological grade had an increased risk of mortality. A survival benefit was captured in females and patients with posterior fossa tumors. Adjuvant radiotherapy and chemotherapy did not confer a survival benefit among all patients, even after stratification by tumor grade or anatomical location.